Pemberdayaan Masyarakat Kelurahan Trimulyo Semarang Melalui Program Gerbang Hebat - Mariana Kristiyanti (Patria : Jurnal Pengabdian Kepada Masyarakat, 2021)
The city of Semarang is currently improving to actualize the saying of 'Moving Together Building the City of Semarang to Be Better and Great' both physically and non-physically. One of them is through Gerbang Hebat program. It is an activity in reducing poverty and unemployment, improving public services, gender equality and improving education also health as stated in the Sapta program (Reducing poverty and unemployment, Handling Floods, Improving Infrastructures, Improving Public Services and Gender Equality). UNIMAR AMNI Semarang carried out community service activities at Trimulyo village to support the government of Semarang program. It is not only students/cadets and lecturers who carry out community service activities but also the surrounding community. They are very enthusiastic in participating in implementing various program activities carried out at  Trimulyo village. The activity begins with planting mangrove trees, socializing healthy living in an unhealthy environment, training in cooking and tidying up the environment.The method of implementing the activities used is the method of observation, interviews and literature studies. The observation was held in Trimulyo village, sub-district of Genuk. The data collection was carried out through interview methods and as a reference for implementing community service activities was using the literature study method. With UNIMAR AMNI Semarang Gerbang Hebat program at Trimulyo village of Subdistrict Genuk hoped that it can improve the healthy lifestyles and increase the income of the Trimulyo village community.